Leveraging Instagram Tools to Enhance Customer Retention in EdTech Industry - Kumar, Premjeet; Masvood, Yaaseen (International Journal of Accounting and Economics Studies, 2025)
A key indicator of success and longevity in the dynamic EdTech sector is the percentage of original customers that remain loyal over time. Businesses are recognising the importance of social media, and Instagram in particular, in today’s market to foster stronger ties with customers and respond to their evolving tastes. This research delves into the ways in which EdTech companies are utilising Instagram’s features to retain customers, including Stories, Reels, Live sessions, Polls, and Highlights. Finding out how Instagram helps with community creation, trust, and ongoing learner engagement is the goal of this mixed-method study that interviews users and EdTech marketers in addition to conducting quantitative surveys. Instagram content that is both dynamic and engaging seems to have a substantial impact on user happiness and platform loyalty in the long run, according to the findings. The research finishes with practical suggestions for EdTech companies looking to maximise their Instagram presence for better client retention.